RESPONSES OF RECOMBINANT INBRED LINES OF COWPEA [(VIGNA UNGUICULATA (L.) WALP] TO STRIGA GESNERIOIDES INFESTATION IN GHANA - Aaron T. Asare; Isaac K. A. Galyuon; Francis K. Padi; Emmanuel P. Otwe; J.F. Takrama (European Scientific Journal, ESJ, 2013)
Cowpea [Vigna unguiculata (L.) Walp.] production in West Africa is constraint by Striga gesnerioides parasitism associated with 83-100% yield loses which warrants development of resistance varieties against the parasite. An exotic resistant genotype, IT97K-499-35 developed by International Institute of Tropical Agriculture (IITA) was crossed with SARC-LO2, a local susceptible genotype. SSR-1 and C42-2B markers previously mapped in the region of S. gesnerioides resistance loci were used to amplify genomic DNA of advance recombinant inbred lines (RILs) of this cross. The responses of the RILS to Striga infection in pot culture and a field trial conformed to segregation ratio of resistance to susceptible genotypes of 1:1 among F7 progenies suggesting monogenic dominant inheritance of the resistance. The markers SSR-1 and C42-2B mapped in the region of the resistance locus, but presented as dominant markers, with amplification only in resistant genotypes. The selective efficiency of SSR-1 (92.6%) was better than that of C42-2B (85.7%). In field trials, growth and morphology of susceptible genotypes were adversely affected by S. gesnerioides which resulted in significant (P ≤ 0.05) reduction in seed yield compared to resistant genotypes. The resistant RILs identified in the current work would be further evaluated in multi-location trials prior to their release to farmers for cultivation.